The Effect of Minimum Wage on Unemployment in North Kalimantan - Kurniawan; Rahmat; Lio Bijumes; Rozilee Asid; Mince Angreyani; Vincente Manuel Luis Guterres (Faculty of Economics and Business, Hasanuddin University, Makassar, Indonesia, 2025)
The annual minimum wage changes cause shifts in the labor market equilibrium. In a competitive labor market, the demand and supply of minimum wages result in a new minimum wage each year. There is no clear evidence regarding the impact of the minimum wage on unemployment. The purpose of this study is to provide evidence on the impact of the minimum wage on unemployment in North Kalimantan. This evidence offers insights for policymakers in setting the minimum wage. This study was conducted using an ordinary least squares (OLS) approach. This study used aggregate data from five sample districts/cities in North Kalimantan province for the period 2017–2024. This study provides strong evidence that the minimum wage has a positive but insignificant effect on unemployment in North Kalimantan. This finding highlights the need for appropriate minimum wage determination, taking into account the efficiency wage theory, which encourages workers to accept better wages. The implication of this study is that annual minimum wage increases do not significantly reduce labor demand and increase unemployment in North Kalimantan.